A study on affordable housing within Malaysia Housing Price Index among the middle income households (MHPI) / Nurul Syafi’qa Mazlan - Mazlan, Nurul Syafi’qa (Faculty of Business and Management, 2017)
The objectives of this study is to investigate the factors may influence Malaysia Housing Price Index among the middle income households. This study decided to choose Malaysia Housing Price Index among the middle incomes households as a dependent variable meanwhile the independent variables are base lending rate, consumer price index, population and household income. The sample of study consists of 8year started 2007 until 2015 and 33 of observation of data in data stream. Type of this study used is secondary data and cover the period from 2007 until 2015. In order to determine the most factors that influence between those variables in Malaysia Housing Price Index among the middle income households. Therefore the result of this study shows that base lending rate, consumer price index, population and household income has significant relationship with Malaysia Housing Price Index among the middle income households. In conclusion, it will be important the most factors influence to use in Malaysia Housing Price Index among the middle income households.